2010
DOI: 10.1103/physrevb.81.224101
|View full text |Cite
|
Sign up to set email alerts
|

Effects of volume mismatch and electronic structure on the decomposition of ScAlN and TiAlN solid solutions

Abstract: Thin solid films of metastable rocksalt structure ͑c-͒ Sc 1−x Al x N and Ti 1−x Al x N were employed as model systems to investigate the relative influence of volume mismatch and electronic structure driving forces for phase separation. Reactive dual magnetron sputtering was used to deposit stoichiometric Sc 0.57 Al 0.43 N͑111͒ and Ti 0.51 Al 0.49 N͑111͒ thin films, at 675°C and 600°C, respectively, followed by stepwise annealing to a maximum temperature of 1100°C. Phase transformations during growth and annea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
38
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 45 publications
(40 citation statements)
references
References 33 publications
2
38
0
Order By: Relevance
“…For instance, it has been found that metastable nitride alloys might phase separate both by a spinodal-decomposition mechanism, for instance, in TiAlN, 26,27 and by nucleation and growth as in ScAlN. 28 The difference has been explained in terms of volume mismatch, favoring nucleation and growth, and the electronic structure as driving forces for phase separation, allowing for spinodal decomposition. [29][30][31] These decomposition mechanisms give a)…”
Section: à3mentioning
confidence: 99%
“…For instance, it has been found that metastable nitride alloys might phase separate both by a spinodal-decomposition mechanism, for instance, in TiAlN, 26,27 and by nucleation and growth as in ScAlN. 28 The difference has been explained in terms of volume mismatch, favoring nucleation and growth, and the electronic structure as driving forces for phase separation, allowing for spinodal decomposition. [29][30][31] These decomposition mechanisms give a)…”
Section: à3mentioning
confidence: 99%
“…It has been theoretically predicted that epitaxial stabilization of ScxAl1-xN up to x=0.4 could hinder the material disintegration through spinodal decomposition [8]. However, phase separation through nucleation and growth of semicoherent wurtzite AlN phases in domain boundaries of cubic ScN has been demonstrated during annealing of cubic solid solutions [14] and might be a limiting factor for alloy formation during thin film growth.…”
Section: Introductionmentioning
confidence: 99%
“…This motivates us to undertake computational investigation of these challenging problems. Moreover, even though nitrogen vacancies are the most common type of defect in binary TM nitrides, experiments indicate that migration of metal vacancies may be the mechanism which primarily controls spinodal decomposition of (Ti,Al)N pseudobinary * davide.gambino@liu.se alloys at high (>1000 K) temperatures [30,31]. Titanium nitride (TiN), the prototype and most studied among all TM nitrides [32], crystallizes in the cubic B1 lattice structure over a wide range of temperatures (from 0 K up to its melting point, T m ≈ 3250 K [33]) and a wide range of stoichiometries TiN x , with 0.6 < x < 1.2 [16].…”
Section: Introductionmentioning
confidence: 99%